Pengaruh Model Pembelajaran STAD Dipadu Media Pembelajaran Komik Materi Sistem Pencernaan Manusia terhadap Hasil Belajar Siswa - Siis Werimon; Insar Damopolii; Jan H. Nunaki (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
This study aims to know the effect of Student Team Achievement Division (STAD) learning model combined comic learning media on student achievement. The type of research was a quasi experimental used the nonequivalent control group design. The study population was all students of class VIII SMP N 15 Manokwari, amounting to 84 students. Determination of sample used purposive sampling technique and obtained class VIII A with a number of 29 students (as experiment class) and class VIII B with a number of 26 students (as control class). Data analysis used Mann Whitney Test at 0.05 significant level with the help of SPSS 22 for windows program. The results showed that the significant value of 0.00 <α = 0.05 with the average of student achievement that taught with STAD learning model combined comics of 68.34 higher than in students who were taught by conventional learning model with the average results learning for 54.00. The conclusion, there is an effect of STAD learning model combined with comic learning material of human digestive system on student achievement.